Analysis of Students' Adaptive Reasoning Ability in Solving HOTS Problems Arithmetic Sequences and Series in Terms of Learning Style - Rani Darmayanti; Rahmad Sugianto; Yus Muhammad (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
This study describes students' adaptive reasoning abilities in solving HOTs type questions in Kolb's learning style. The method used to determine students' adaptive reasoning ability in solving HOTS (Higher Order Thinking Skill) uses qualitative research with a descriptive approach and type questions regarding learning styles (diverger, assimilator, converger, and accommodator types). The research subjects were thirty-five students of class XI. The results of data analysis and discussion can be concluded that students of class XI MIPS-3 SMA Negeri 4 Pasuruan have adaptive reasoning abilities in solving solutions to the HOTS type questions through the Polya step in terms of Kolb's learning style. Students who have adaptive reasoning ability solve the HOTS type problem solving through the Polya step in terms of Kolb's learning style. Students with a converger type of learning style can meet all indicators of adaptive reasoning ability (propose conjectures or conjectures, provide reasons or evidence about the truth of a statement, draw conclusions from an idea, check the validity of an argument, and find patterns from a mathematical problem) and all indicators in the Polya step (understand the problem, make a plan, implement the plan and re-examine the results).